PENGEMBANGAN MODUL MOMENTUM, IMPULS DAN TUMBUKAN DENGAN STRATEGI CONCEPT MAPPING DI MADRASAH ALIYAH NEGERI - Siti Rudlotus Sa'diah; Trapsilo Prihandono; Sri Wahyuni (FKIP Universitas Jember, 2018)
AbstractOne of physics material’s character was abstract, that charactercaused the students got difficulties. Besides that, the unconsecutive materialwas becomes a weakness in the displays of material in physics books at school.One of solution to solve this problems was using the concept mapping module.The purposes of this research were to describe the validity of modules,effectiveness, and practicality. The research method used was 4D model whichsuggested by Thiagarajan, Semmel and Semmel. The result of this researchwas module classified as valid by the value of validity was 85,47%, modulewas effective by value of retention 98,79%, module classified as practical byvalue of student response was 67,71%. Based on these data, it can beconcluded that the module was very valid, effective and practical for used inlearning.Keyword: module, concept mapping, 4D model